Effects of sulfur-based hemostatic agents and gingival retraction cords handled with latex gloves on the polymerization of polyvinyl siloxane impression materials (Journal of Applied Oral Science, 2011)
OBJECTIVES: This study investigated the possible interactions between three addition silicone materials (Express®, Aquasil Ultra® and Adsil®), three hemostatic agents (ferric sulfate, StatGel FS®; aluminum sulfate, GelCord®; and aluminum chloride, Hemostop®) and gingival retraction cords previously handled with latex gloves to determine whether direct contact with medicaments or indirect contamination by latex in conditions similar to those found in clinical practice inhibit or affect the setting of the impression materials. MATERIAL AND METHODS: A portable device for the simultaneous test of several specimens was specifically developed for this study. Polymerization inhibition was analyzed by examination of the impressions and the molded surface. Ten trials were performed for each addition silicone material used in the study, at a total of 240 study samples. RESULTS: All the samples tested (N=240) were nonreactive regardless of the type of combination used. CONCLUSIONS: Aluminum sulfate, ferric sulfate and aluminum chloride hemostatic solutions did not show any inhibitory potential on the addition silicone samples under study, and there were no changes in polymerization as a result of contact between addition silicone and retraction cords handled with latex gloves.